Critical thinking and criticism of thought. A journey into the human essence in times of crisis - Idana Beroska Rincón Soto, (Revista de Filosofía, 2024)
The study aims to explore the critique of critical thinking in the context of artificial intelligence (AI) and its impact on humanity. It seeks to understand how AI can affect our critical reasoning capacities and the meaning of our human essence in a society increasingly dominated by technology.Methodology: A multidisciplinary approach is adopted that integrates perspectives from philosophy, psychology, education, and ethics. Theoretical and empirical studies that address critical thinking and the influence of AI on social dynamics are reviewed. The ethical and philosophical implications of automation and the use of algorithms in decision-making are analyzed.Conclusions: The analysis suggests that AI, while having the potential to improve efficiency in various fields, also poses significant risks to human autonomy and critical thinking ability. It concludes that education should be adapted to include the development of critical and ethical thinking, ensuring that individuals maintain a sense of humanity in the digital age. The need for policies that promote a harmonious coexistence between AI and fundamental human values is emphasized.